(untitled) (Jurnal Penelitian Kehutanan Wallacea, 2013)
Acacia crassicarpa improved seed has a higher quality than unimproved seed. To maintain the viability, improved seeds are required as appropriate handling techniques. One of the important steps in seed handling is seed germination test. A. crassicarpa seed have dormancy and to break it needs specific pretreatment. Germination test can be worked in the laboratory and greenhouse. The purpose of this research was to obtain pretreatment and germination method better to maintain the viability of A. crassicarpa improved seed. Pretreatment in resources were without treatment, soaking in hot water (100oC ) and followed by soaking for 24 hours in cold water, soaking for 1 minute in hot water (100oC) followed by soaking for 24 hours in cold water, soaking for 6 minutes in hot water (100oC) followed by soaking for 24 hours in cold water, soaking for 30 minutes in H2SO4 , torn of seedcoat, and torn of seedcoat and then soaking for 24 hours in cold water. Laboratory Germination method were top of paper (TP), between paper (BP), and pleated paper (PP) test. Whereas growing media used in greenhouse were top soil, sand, a mixture of top soil and sand (1:1/v:v), and cocopeat. The results showed that to maintain the viability of A. crassicarpa improved seed required the best pretreatment technique and germination methods were (1) in laboratory used combine between torn of seedcoat and top of paper. In this method, the percent of seed germination reached 96 %, and (2) in greenhouse used combine between torn of seedcoat and cocopeat. In this method, the percent of seed germination reached 88 %.